Capacitance-Voltage Characteristics of Nanowire Trigate MOSFET Considering Wave Function Penetration - Md. Alamgir Hossain; Arif Mahmud; Mahfuzul Haque Chowdhury; Md. Mijanur Rahman (International Journal of Electrical and Computer Engineering (IJECE), 2012)
Short channel  effects on the gate capacitance of nanowire trigate MOS field-effect transistors are studied considering wave function penetration. Capacitance-Voltage (C‑V) measurements are commonly used in studying gate-oxide quality in detail.  C‑V test results offer a wealth of device and process information, including bulk and interface charges. Capacitance indicates switching speed of the MOSFET. It is our goal to minimize capacitance as possible as we can in MOSFET. Due to our necessary to compact the Integrated Circuit as possible as we can for getting small electronics devices. Capacitance determines the speed of the IC. Every engineer in this section should know capacitance of his implementing device MOSFET to get exact result from this device. Whenever we deal with 10X10 nm scale or less device of MOSFET. We must concern the effect of wave function penetration into device in this stage classical mechanics fails to describe exact result of the system because electron can move in only one direction (x), in 3 Dimension, it cannot move in other two direction (y, z). i.e. confined in two direction which is not predictable by classical mechanics here quantum mechanics (QM) gives better solution of this problem. Therefore we consider QM in our study. Here we presented how wave function play vital role considering small area of trigate MOSFET. It is the analytical approach of QM and highly recommendation to use QM rather than CM to get accuracy. This result will be helpful for determining capacitance of trigate MOSFET.DOI:http://dx.doi.org/10.11591/ijece.v2i6.1785